Kikuchi‐Fujimoto disease: A rare case report from Nepal. Issue 10 (28th October 2021) - Rauniyar, Rahul; Acharya, Kshitiz; Mishra, Aman; Pathak, Nibesh; Chaudhary, Gajendra; Bhandari, Puja; Gaire, Prabin
Abstract: Clinicians and pathologists must be aware of the occurrence of Kikuchi‐Fujimoto Disease, as one of the differential diagnoses of cervical lymphadenopathy. Abstract : Clinicians and pathologists must be aware of the occurrence of Kikuchi‐Fujimoto Disease, as one of the differential diagnoses of cervical lymphadenopathy.